Ecological Literacy And Ecological Environmental Concern On The Implementation Of Green Economy Policy In Grobogan District MSMEs - Rosita, Dian; Nadhifah, Tuti; Risnawati, Heni; Muttaqin, Ibnu (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2024)
The aim of this research is to examine the influence of ecological literacy and environmental awareness on the implementation of green economy policies in Grobogan Regency MSMEs. The research method used is quantitative research. The sampling technique is purposive sampling which has criteria for MSME business actors in Grobogan Regency who operate in the food and beverage sector. Data collection uses a questionnaire distributed directly to respondents. The research results simultaneously show that ecological literacy and environmental concern influence the implementation of Green Economy policies. Partially, ecological literacy and environmental concern influence the implementation of green economy policies in Grobogan Regency MSMEs.